PERAN ISTRI BURUH TANI KARET DALAM MENINGKATKAN EKONOMI KELUARGA ( STUDI DI DESA LALANG KECAMATAN SUNGAI APIT KABUPATEN SIAK ) - Desi Musalmah; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Ball cutter’s wife activity is important for increase famaly’s economy. The kind of activities is do also such as Taylor, Nunny Act. The thing of being motivation for ball cutter’s wife in order her family is good. Time for work is not disturb her duty as wife in family. And the the all of family is are cooperate for being kind family.Key words: Neccesary, Economy